2015
DOI: 10.1111/1365-2656.12409
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modelling of habitat selection by marine predators with respect to the abundance and depth distribution of pelagic prey

Abstract: Summary 1.Understanding the ecological processes that underpin species distribution patterns is a fundamental goal in spatial ecology. However, developing predictive models of habitat use is challenging for species that forage in marine environments, as both predators and prey are often highly mobile and difficult to monitor. Consequently, few studies have developed resource selection functions for marine predators based directly on the abundance and distribution of their prey. 2. We analysed contemporaneous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 70 publications
(140 reference statements)
2
54
0
Order By: Relevance
“…Acoustic survey data revealed contrasting foraging conditions in terms of the regional abundance, depth distribution and spatial configuration of anchoveta in early December 2008 and 2009 (Boyd et al . ,b; Fig. ).…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Acoustic survey data revealed contrasting foraging conditions in terms of the regional abundance, depth distribution and spatial configuration of anchoveta in early December 2008 and 2009 (Boyd et al . ,b; Fig. ).…”
Section: Methodsmentioning
confidence: 92%
“…One hundred Bayesian posterior predictions of the abundance and depth distribution of anchoveta in each grid cell were generated based on acoustic survey data for 2008 and 2009 (Boyd et al . ,b). Eight sets of 100 simulated prey fields were then constructed from the Bayesian posterior predictions, representing the eight possible combinations of high or low regional abundance with shallow or deep depth distributions and broad or concentrated spatial configurations (see Appendix S2 for further details.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals dove more often when prey were located at shallow depth, but not necessarily when the relative abundance of prey was higher Boyd et al, 2015 parameters. A major advantage of biologging is the potential to estimate food supply over multiple spatial and temporal scales.…”
Section: Phalacrocorax Bougainvilliorummentioning
confidence: 94%
“…The consensus from the studies in Table 1 is that biologgers are useful tools that demonstrate how seabirds adjust their foraging behavior to fish stocks and distribution, sometimes showing strong correlations (Litzow and Piatt, 2003;Bertrand et al, 2012;Cohen et al, 2014;Boyd et al, 2015). Three studies found a linear correlation between fish stocks and foraging parameters (Litzow and Piatt, 2003;Bertrand et al, 2012;Cohen et al, 2014), which suggests that foraging distance from the colony, diving depth, and diving activity may be good candidate parameters for detection of changes in food supply.…”
Section: Use Of Biologger-derived Behaviors As Indicators Of Food Supplymentioning
confidence: 99%